2010
DOI: 10.1007/s11090-010-9241-8
|View full text |Cite
|
Sign up to set email alerts
|

Packed Bed DBD Discharge Experiments in Admixtures of N2 and CH4

Abstract: The physical, chemical and electrical properties of a coaxial Dielectric Barrier Discharge (DBD) fed by various mixtures of N 2 and CH 4 at atmospheric pressure and ambient temperature has been studied. FTIR spectral measurements of the products formed in the discharge have shown that the main chemical products are C 2 H 2, HCN and C 2 H 6 produced by dissociation of CH 4 , with small but significant traces of NH 3 .such a chemical transformation may provide some insight into the chemical processes prevalent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…The latter are the most efficient processes to produce solid material named tholins. Several discharges have been used up to now: Direct Current discharges (DC) (Khare et al, 1984), barrier discharges (Horvath et al, 2010), corona discharges (Horvath et al, 2009), Radio frequency discharges Inductively coupled (Imanaka et al, 2004) or capacitively coupled as what was used in the present work on the PAMPRE reactor (Szopa et al, 2006). In the PAMPRE reactor tholins are produced as powder (Szopa et al, 2006) or as thin films on substrates (Quirico et al, 2008;Sciamma-O'Brien et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The latter are the most efficient processes to produce solid material named tholins. Several discharges have been used up to now: Direct Current discharges (DC) (Khare et al, 1984), barrier discharges (Horvath et al, 2010), corona discharges (Horvath et al, 2009), Radio frequency discharges Inductively coupled (Imanaka et al, 2004) or capacitively coupled as what was used in the present work on the PAMPRE reactor (Szopa et al, 2006). In the PAMPRE reactor tholins are produced as powder (Szopa et al, 2006) or as thin films on substrates (Quirico et al, 2008;Sciamma-O'Brien et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The production of HCN increased with input power (see rows [1][2][3][4][5] in the presence of CO 2 and CH 4 , but showed no dependence upon power in the experiments using just CH 4 and N 2 (rows 6-10). The study of the plasma driven conversion of CH 4 /N 2 mixtures is topical due to their relevance to the atmospheres of Titan and Triton (and the postulate that these are models for the early development of Earth) [70][71][72] and also with respect to natural gas conversion [73]. Horvath et al [72] have observed HCN at similar concentrations using the same SIE as here: thus the authors employed a cylindrical, co-axial quartz reactor packed with borosilicate beads and supplied with 10%CH 4 /N 2 at SIEs of 1-30 kJ dm -3 .…”
Section: Data Manipulationmentioning
confidence: 99%
“…The gas phase production of HCN in the plasma region is most likely produced by the following mechanism [72]. the initial step is electron impact reaction with CH 4 which requires electron energies greater than 10 eV.…”
Section: Data Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of an electric discharge on highly reducing gas mixtures of methane (CH 4 ), nitrogen (N 2 ), and ammonia (NH 3 ) with water vapour has been shown to result in the synthesis of many different biologically important organic compounds including amino acids . It has been also shown that ammonia can be produced in discharges at atmospheric pressure and it is assumed that ammonia can be created by reactions on surfaces . Such electrical discharges are believed to imitate the effect of thunderstorm lightning on chemical processes in prebiotic atmospheres; indeed, the Miller–Urey spark discharge experiments in the early 1950s were the first experimental studies describing the results in reducing atmospheres and led to the start of laboratory studies of the origins of prebiotic material on the Earth.…”
Section: Introductionmentioning
confidence: 99%